On the role of aggregation effects in the performance of perylene-diimide based solar cells - Singh, Ranbir; Giussani, Ester; Mróz, Marta M.; Di Fonzo, Fabio; Fazzi, Daniele; Cabanillas-González, Juan R.; Oldridge, Luke; Vaenas, Naoum; Kontos, Athanassios G.; Falaras, Polycarpos; Grimsdale, Andrew C.; Jacob, Josemon; et al. (My University, 2014)
A model bulk-heterojunction of a perylene diimide (PDI) monomeric derivative is studied for interrogating the role of PDI aggregates in the photocurrent generation efficiency (ηPC) of PDI-based organic photovoltaic (OPV) devices. Blend films of the PDI derivative and the poly(indenofluorene) (PIF) polymer annealed between room temperature and 220 °C, are used as the photoactive layers for the fabrication of OPVs. The positive effect of thermal annealing is assigned to the evolution of PDI aggregates in the amorphous PIF matrix. Annealing increases the electron mobility by three orders of magnitude. In contrast, owned to the thermally inert PIF matrix used, hole mobility increases only by a factor of six. High resolution cross-sectional scanning electron microscopy suggests that ηPC in PDI-based OPVs is not limited by the PDI aggregates but by their improper alignment. In situ Raman spectra and density functional theory calculations identify a marker for monitoring the strength of π-π stacking interactions between PDI monomers. It s further demonstrated that the electron-collecting electrode of the PIF:PDI devices dictates their performance. The use of Al is found to impede charge extraction and this is attributed to an unidentified product of the reaction between PDI and Al that leads to the formation of an electron-blocking layer. Device performance rectifies when a Ca/Al electrode is used and the power conversion efficiency is increased by a factor of four. © 2014 Elsevier B.V. All rights reserved.
Keywords: Non-fullerene acceptors; Perylene diimide; Aggregation; Charge transport; Morphology; Organic solar cells